Conservation Status and Population Density of Himalayan Serow (Capricornis sumatraensis) in Annapurna Conservation Area of Nepal - Aryal, Achyut (The Initiation, 2010)
Himalayan Serow ‘Capricornis sumatraensis' population is isolated in a small patch of the southern part of Annapurna Conservation Area (ACA) with a population density of 1.17 individual/km2 and a population sex ratio of 1:1.6(Male: Female). A strong correlation was found between population (y) and pellets density (x) (y=0.011x-0.2619, R2-0.97). The major problems in the Serow habitat were habitat fragmentation & land use change, conflict between predator and villager, livestock grazing and poaching. The study was successful in providing information on the present status of Himalayan Serow in the ACA Key Words: Population density, Sex ratio, Fragmentation, Conservation, Threats DOI: 10.3126/init.v3i0.2423 The Initiation Vol.3 2009 p.12-19